The Influence of Social Media Marketing, Service Quality and Store Atmosphere on Consumer Purchase Decision Using Brand Image as Intervening Variable at PT. Berjaya Sally Ceria, Sour Sally – Cemara Asri - Depari, Genesis Sembiring; Jocellyn, Jocellyn (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine the influence of social media marketing, service quality and store atmosphere on consumer purchase decisions by using Brand Image as an intervening variable. In this study, the author uses a quantitative research design and SPSS. The author uses descriptive and causal research. The sampling technique used is convenience sampling. The sample size is 110 customers. The results of the hypothesis test show that Social Media Marketing has an effect on Brand Image and Service Quality has an effect on Consumer Purchase Decisions. Service Quality and Store Atmosphere have no effect on Brand Image, Store Atmosphere has no effect on Consumer Purchase Decisions and Brand Image does not mediate the influence of social media marketing, service quality and store atmosphere on Consumer Purchase Decisions.